Training Mentors of Clinical and Translational Research Scholars: A Randomized Controlled Trial - Pfund, Christine (2014)
PURPOSE: To determine whether a structured mentoring curriculum improves research mentoring skills. METHOD: The authors conducted a randomized controlled trial (RCT) at 16 academic health centers (June 2010 to July 2011). Faculty mentors of trainees who were conducting clinical/translational research ≥50% of the time were eligible. The intervention was an eight-hour, case-based curriculum focused on six mentoring competencies. The primary outcome was the change in mentors’ self-reported pretest to posttest composite scores on the Mentoring Competency Assessment (MCA). Secondary outcomes included changes in the following: mentors’ awareness as measured by their self-reported retrospective change in MCA scores, mentees’ ratings of their mentors’ competency as measured by MCA scores, and mentoring behaviors as reported by mentors and their mentees. RESULTS: A total of 283 mentor–mentee pairs were enrolled: 144 mentors were randomized to the intervention; 139 to the control condition. Self-reported pre-/posttest change in MCA composite scores was higher for mentors in the intervention group compared with controls (P < .001). Retrospective changes in MCA composite scores between the two groups were even greater, and extended to all six subscale scores (P < .001). More intervention-group mentors reported changes in their mentoring practices than control mentors (P < .001). Mentees working with intervention-group mentors reported larger changes in retrospective MCA pre-/posttest scores (P = .003) and more changes in their mentors’ behavior (P = .002) than those paired with control mentors. CONCLUSIONS: This RCT demonstrates that a competency-based research mentor training program can improve mentors’ skills.